2020
DOI: 10.9734/ejnfs/2020/v12i130180
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wet and Dry Seasons on the Distribution of Polycyclic Aromatic Hydrocarbons in Selected Vended Street Foods in Parts of Port Harcourt Metropolis

Abstract: The distribution patterns of PAHs in selected ready-to-eat street foods in parts of Port Harcourt metropolis was investigated during wet and dry seasons in 3 locations (Makoba-station 1, Elekahia-station 2 and Rivers State University-station 3). The study was carried out using a complete randomized design in three factorial experiments (Factors A, B and C). Factor A represented Season, B Location and C Street Vended foods samples. The selected food samples were Roasted plantain (RP1-3), Roasted Fish (RF1-3), R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Three (3) factorials were used (Factors A, B and C, with factor A as season, B as location and C as street vended foods samples) given as 2X3X3 factorials. The experimental design of the study is shown in Table 1 using the previous method of Oyet et al (2020).…”
Section: Experimental Designmentioning
confidence: 99%
“…Three (3) factorials were used (Factors A, B and C, with factor A as season, B as location and C as street vended foods samples) given as 2X3X3 factorials. The experimental design of the study is shown in Table 1 using the previous method of Oyet et al (2020).…”
Section: Experimental Designmentioning
confidence: 99%
“…Two factorials were used (Factors A and B); factor A represented Location and B StreetVended food samples given as 3×8 factorials. The vended foods are as shown in Table 1, [41].…”
Section: Experimental Designmentioning
confidence: 99%